Modifikasi Limbah Tulang Sapi Bali dan Pemanfaatannya untuk Adsorpsi Methylene Blue (MODIFICATION OF BALI COW BONE WASTE AND ITS APPLICATION TO ADSORPTION OF METHYLENE BLUE) - Simpen, I Nengah; Suastuti, Ni Gusti Ayu Made Dwi Adhi (Jurnal Veteriner, 2017)
The research of modification, characterization, and application of nano-porous adsorbent base onBali cow bone waste to methylene blue (MB) adsorption has been carried out. The modification was carriedout through extraction of hydroxyapatite (HA) from cow bone, then its activated by 0.4 M NaOH solutionand coating to form active sites of Fe and Fe-Al oxides. The adsorbent was applied to know quantitativelyadsorption capacity coated-HA (CHA) to MB as wastewaters simulation. Compound of CHA wascharacterized amount of active sites by base-acid titration, Bronsted-Lewis acid sites by FTIR spectroscopy,specific surface area by MB method and pore size by surface area analyzer gasorption nitrogen. While,amount of coated-Fe and Al by LIBS. Amount of MB adsorbed was analyzed by UV-Vis spectrophotometer.The results showed that coating of Fe and Fe-Al oxides increased amount of active sites, sites distributionof new Lewis acid site, everage nano pore size with pore volume is microporous (less than 2 nm), and Fe andFe-Al oxides was into HA crystal structure. The amount of active sites was the higest of T1-Fe-Al2O3 andall pores diameter less than 58.182 nm.While, the specific surface area increased T3-Fe2O3>T3-Fe-Al2O3>T2-Fe2O3 respectively. In the adsorption isotherm, coating on HA significantly increased ability of adsorbentand through Freundlich model (R2 > 0.77) with the higest adsorption capacity on T3-Fe2O3 (3.2019 mg/g)then T2-Fe-Al2O3 (2.7921 mg/g). Results of this research indicate that Fe and Fe-Al oxides HA-modifiedincreased adsorption ability.
Keywords: cow bone; hydroxyapatite; adsorption; methylene blue